Exercise Training Favorably Modulates Gene and Protein Expression That Regulate Arterial Cholesterol Content in CETP Transgenic Mice - Pinto, Paula R.; da Silva, Karolline S.; Iborra, Rodrigo T.; Okuda, Ligia S.; Gomes-Kjerulf, Diego; Ferreira, Guilherme S.; Machado-Lima, Adriana; Rocco, Debora D. F. M.; Nakandakare, Edna R.; Machado, Ubiratan F.; Correa-Giannella, Maria L.; Catanozi, Sergio; et al. (Frontiers in Physiology, 2018)
Aerobic exercise training (AET) improves the reverse cholesterol transport (RCT) in cholesteryl ester transfer protein-transgenic (CETP-tg) mice. We aimed at investigating the role of AET in the expression of genes and proteins involved in lipid flux in the aorta and macrophages of CETP-tg mice. Three-month-old male mice were randomly divided into trained (T; treadmill 15 m/min; 30 min/day) and sedentary (S) groups. After 6 weeks, peritoneal macrophages and the aortic arch were obtained immediately (0h) or 48 h after the last exercise session. mRNA was determined by RT-qPCR, protein levels by immunoblot and 14C-cholesterol efflux determined in macrophages. AET did not change body weight, plasma cholesterol, triglycerides, glucose and CETP activity. In macrophages, at time 0 h, a higher expression of genes that encode PPAR gamma, ABCA-1 and a lower expression of MCP-1 and IL-10, was observed in T as compared to S. After 48 h, lower expressions of MCP-1 and PPAR gamma genes were observed in T mice. Increase in ABCA-1, SR-BI and IL-6 and a decrease of LOX-1, MCP-1, TNF and IL-10 gene expression was observed in the aorta of T compared to S mice (0h) and LOX-1 and MCP-1 remained diminished after 48 h. The protein level of MCP-1 and SR-BI in the aortic arch was unchanged in T animals after 48 h as compared to S, but LOX-1 was reduced confirming data of gene expression. The apo A-I and the HDL2 mediated-cholesterol efflux (8 and 24 h) were not different between T and S animals. In the presence of CETP, AET positively influences gene expression in the arterial wall and macrophages of CETP-tg mice contributing to the RCT and prevention of atherosclerosis. These changes are perceptible immediately after the exercise session and are influenced by the presence of CETP although independent of changes in its activity. Reductions in gene and protein expression of LOX-1 were parallel and reflect the ability of exercise training in reducing the uptake of modified LDL by the arterial wall macrophages.